Harnessing the potential of mutation breeding, CRISPR genome editing, and beyond for sustainable agriculture - Nor A’azizam, Nelissa Maisara; Chopra, Sakshi; Guleria, Praveen; Kumar, Vineet; Abd Rahim, Muhamad Hafiz; Yaacob, Jamilah Syafawati (Institute for Ionics, 2024)
By 2050, the global population is projected to exceed 9.5 billion, posing a formidable challenge to ensure food security worldwide. To address this pressing issue, mutation breeding in horticultural crops, utilizing physical or chemical methods, has emerged as a promising biotechnological strategy. However, the efficacy of these mutagens can be influenced by various factors, including biological and environmental variables, as well as targeted plant materials. This review highlights the global challenges related to food security and explores the potential of mutation breeding as an indispensable biotechnological tool in overcoming food insecurity. This review also covers the emergence of CRISPR-Cas9, a breakthrough technology offering precise genome editing for the development of high-yield, stress-tolerant crops. Together, mutation breeding and CRISPR can potentially address future food demands. This review focuses into these biotechnological advancements, emphasizing their combined potential to fortify global food security in the face of a booming population.